2012
DOI: 10.1002/bsl.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluator Agreement in Placement Recommendations for Insanity Acquittees

Abstract: Research has examined differences between psychologists and psychiatrists in opinions on trial competency and criminal responsibility, but there is little research on such differences in risk assessment. This study examined the impact of disciplinary affiliation on opinions regarding whether new insanity acquittees should be hospitalized or released, and the risk factors given the most weight by each discipline. There was no significant difference between disciplines in the frequency of recommendations for hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
16
1
Order By: Relevance
“…Triads of evaluators on the same case showed disagreement levels between 50% and 60% (McNichols, Gowensmith et al, ; Nguyen et al, ). Further, pairs of evaluators in Virginia disagreed on 22% of cases in which evaluators were deciding if new insanity acquittees should be hospitalized or placed in the community on CR (Stredny, Parker, & Dibble, ). Overall, research suggests that forensic evaluators do not consistently agree upon issues related CR readiness.…”
Section: Evaluating Readiness For Conditional Releasementioning
confidence: 99%
See 2 more Smart Citations
“…Triads of evaluators on the same case showed disagreement levels between 50% and 60% (McNichols, Gowensmith et al, ; Nguyen et al, ). Further, pairs of evaluators in Virginia disagreed on 22% of cases in which evaluators were deciding if new insanity acquittees should be hospitalized or placed in the community on CR (Stredny, Parker, & Dibble, ). Overall, research suggests that forensic evaluators do not consistently agree upon issues related CR readiness.…”
Section: Evaluating Readiness For Conditional Releasementioning
confidence: 99%
“…McDermott et al () reviewed 81 CR cases in California and observed that evaluators considered several empirically‐supported risk factors for violence, such as acquittees’ substance use, adherence to clinical treatment, and structured violence risk assessment information. Stredny et al () found that psychiatrists and psychologists relied on different sets of factors when formulating their release decisions, and that moderate variability existed in the factors that evaluators prioritized in the initial commitment of insanity acquittees in Virginia. For example, psychiatrists in their study prioritized substance abuse history and family/psychosocial issues more than psychologists, while psychologists prioritized use of weapons more often than psychiatrists.…”
Section: What Influences Conditional Release Decisions?mentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed that older age at first criminal offense predicted transfer, a finding previously suggested by Hilton and Simmons (), who observed that severity of criminal history informed clinicians' assessments. Stredny, Parker, and Dibble () likewise identified that the instant offense (specifically, whether offenses involved the use of weapons) impacted the decision‐making of evaluators.…”
Section: Factors Relevant In Evaluators' Opinions Regarding Transfermentioning
confidence: 99%
“…For example, in an archival review of patient files and release decisions over a 30 year period, McDermott and colleagues () found that treatment compliance and responsiveness, substance use, and risk of violence were the most relevant factors considered in decisions regarding release of NGRI acquittees from forensic institutions. Other studies highlight the relevance of insight, personal support, symptoms of mental illness, family conflict, social withdrawal (McKee, Harris, & Rice, ), medication compliance (Hilton & Simmons, ), and presence of structured activities in the community (Stredny et al , ) in decision‐making.…”
Section: Factors Relevant In Evaluators' Opinions Regarding Transfermentioning
confidence: 99%